Structure of Tetrahymena CCTθ gene and its expression under colchicine treatment - Domingues, Célia (2018)
We report here the cloning and the characterization of the Tetrahymena pyriformis chaperonin-containing-TCP1 theta gene (TpCCTθ), an orthologue of the mouse chaperonin gene CCTθ. TpCCTθ gene is interrupted by eight introns, ranging in size between 91 and 419 nucleotides, and encodes a protein consisting of 540 amino acid residues (59.1 kDa), with a putative pI of 5.73. The amino acid sequence of TpCCTθ reveals 39.4–46.0% identity with the sequences of Candida albicans and mouse CCTθ subunits and 28.0–32.6% identity with the other TpCCT subunits known so far. We have studied the expression of this gene in exponentially growing Tetrahymena cells and in cells treated with colchicine for different times. The steady-state levels of CCTθ mRNA rapidly decrease in the first 30 min of colchicine treatment. Interestingly, treatment for subsequent 60 min gives expression levels higher than those found in exponentially growing cells.